Balance between activating NKG2D, DNAM‐1, NKp44 and NKp46 and inhibitory CD94/NKG2A receptors determine natural killer degranulation towards rheumatoid arthritis synovial fibroblasts. Issue 4 (August 2014) - Nielsen, Natasja; Pascal, Veronique; Fasth, Andreas E. R.; Sundström, Yvonne; Galsgaard, Elisabeth D.; Ahern, David; Andersen, Martin; Baslund, Bo; Bartels, Else M.; Bliddal, Henning; Feldmann, Marc; Malmström, Vivianne; et al.
Summary Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and synovial hyperplasia leading to progressive joint destruction. Fibroblast‐like synoviocytes (FLS) are central components of the aggressive, tumour‐like synovial structure termed pannus, which invades the joint space and cartilage. A distinct natural killer (NK) cell subset expressing the inhibitory CD94/NKG2A receptor is present in RA synovial fluid. Little is known about possible cellular interactions between RA‐FLS and NK cells. We used cultured RA‐FLS and the human NK cell line Nishi, of which the latter expresses an NK receptor repertoire similar to that of NK cells in RA synovial fluid, as an in vitro model system of RA‐FLS/NK cell cross‐talk. We show that RA‐FLS express numerous ligands for both activating and inhibitory NK cell receptors, and stimulate degranulation of Nishi cells. We found that NKG2D, DNAM‐1, NKp46 and NKp44 are the key activating receptors involved in Nishi cell degranulation towards RA‐FLS. Moreover, blockade of the interaction between CD94/NKG2A and its ligand HLA‐E expressed on RA‐FLS further enhanced Nishi cell degranulation in co‐culture with RA‐FLS. Using cultured RA‐FLS and the human NK cell line Nishi as an in vitro model system of RA‐FLS/NK cell cross‐talk, our results suggest that cell‐mediated cytotoxicity of RA‐FLS may be one mechanism by which NK cells influence local joint inflammation in RA.